Urinary dialkylphosphate metabolites and health symptoms among farmers in Thailand - Ratana Sapbamrer (2018)
© 2017 Taylor & Francis. Using a cross-sectional study, we investigated urinary DAPs levels and health symptoms related to the type of crop cultivation and farm tasks among 84 farmers in Phayao Province of northern Thailand. The results showed that the average of ∑DAPs levels was 10.93 ± 19.64 μg/g creatinine (range 1.48–163.90 μg/g creatinine). The compound found the most was DEP, followed by DETP, DEDTP, DMP, DMTP, and DMDTP, respectively. The type of crop cultivation may be associated with an increasing prevalence of respiratory tract, muscle system, and skin irritation. Farm tasks were associated with an increasing prevalence of muscle system and skin irritation. It was difficult to assess adverse health symptoms associated with urinary DAPs in low levels of exposure; therefore, further investigation is needed using more sensitive biomarkers and more sensitive health symptom measurement.